Molecular Dynamics of Open Systems: Construction of a Mean‐Field Particle Reservoir. Issue 5 (18th March 2019) - Delle Site, Luigi; Krekeler, Christian; Whittaker, John; Agarwal, Animesh; Klein, Rupert; Höfling, Felix
Abstract: The simulation of open molecular systems requires explicit or implicit reservoirs of energy and particles. Whereas full atomistic resolution is desired in the region of interest, there is some freedom in the implementation of the reservoirs. Here, a combined, explicit reservoir is constructed by interfacing the atomistic region with regions of point‐like, non‐interacting particles (tracers) embedded in a thermodynamic mean field. The tracer molecules acquire atomistic resolution upon entering the atomistic region and equilibrate with this environment, while atomistic molecules become tracers governed by an effective mean‐field potential after crossing the atomistic boundary. The approach is extensively tested on thermodynamic, structural, and dynamic properties of liquid water. Conceptual and numerical advantages of the procedure as well as new perspectives are highlighted and discussed. Abstract : A procedure for the construction of a particle and energy reservoir for the simulation of open molecular systems is presented. The reservoir is made of non‐interacting particles (tracers), embedded in a mean‐field. The tracer molecules acquire atomistic resolution upon entering the atomistic region, while atomistic molecules become tracers after crossing the atomistic boundary.